Ingeniería de reservorios geotérmicos - Iglesias Rodríguez, Eduardo; Hiriart L., Gerardo; Cinco Ley, Heber; Córdova M., Francisco; Samaniego, Fernando (My University, 1979)
For a complete analysis of a geothermal system, a model of the flow in the wellbore and in the reservoir is necessary. The equations governing the flow in these two cases are different, so reservoir models based on Darcy-type flow cannot be extended to predict the wellbore flow. Several numerical codes have been written to simulate the two phase flow of steam and water in a geothermal well. Most of these model include the slip between the phases, using experimentally determined values of holdup and friction factora for each particular flow regimen (such as annular or slug).
Keywords: termodinámica; fluidos; presión; símbolos; producción